X-ray powder diffraction analysis of methionine sulfoxide - Corbi, P. P.; Melnikov, P.; Massabni, Antonio Carlos [UNESP] (J C P D S-int Centre Diffraction Data, 2001)
Powder X-ray diffraction data for methionine sulfoxide, C5H11NO3S, obtained from the commercial amino acid, are presented in this work. Monoclinic cell parameters are: a = 15.500 Angstrom; b = 3.820 Angstrom; c = 13.490 Angstrom; 8=97.300 degrees. (C) 2001 International Centre for Diffraction Data.
Keywords: powder diffraction; amino acid; methionine sulfoxide